Vaporization characteristics of ethanol and 1-propanol droplets at high temperatures - Saharin, Sanisah; Lefort, Benoite; Morin, Celine; Chauveau, Christian; Le Moyne, Luis; Kafafy, Raed (Begell House Inc., 2012)
A detailed description of the vaporization of an isolated droplet has been carried out in this experimental study aimed at investigating ethanol and another aliphatic alcohol, 1-propanol. The characterization of the vaporization phenomenon is necessary for this liquid fuel to develop efficient design of injection systems for propulsion and power generation. Particularly, the vaporization rates and their dependency on temperature, important features for modeling and design, are explored for both ethanol and 1-propanol at intermediate to high temperatures. The experimental setup consists of a pressure chamber in which the furnace, the droplet formation, the droplet support, and motion devices are located. An alcohol droplet is located at the intersection of the cross quartz fiber (diameter of 14 μm) with a controlled initial diameter (range of 300-600 μm). Ambient temperature is varied from 298 to 973 K, at atmospheric pressure. The "quasi-steady" theory has been used to compare and to explain all experimental results. The results show that the d 2 law is obeyed and an average vaporization rate is achieved in the case of 1-propanol vaporization. On the other hand, the real impact of the water concentration on the vaporization rate of an ethanol droplet in a large range of temperature is also examined, where two "quasi-steady" periods are observed on the d 2 curves, clearly showing that the vaporization of an ethanol droplet is accompanied by the simultaneous condensation of water vapor on the droplet surface and thus the temporal evolution of the droplet squared diameter exhibits an unsteady behavior. The histories of the instantaneous vaporization rates calculated from the d 2(t) curves of both 1-propanol and ethanol droplets confirm this phenomenon